Systematic Characterization of High-Power Short-Duration Ablation: Insight From an Advanced Virtual Model - Petras, Argyrios; Moreno Weidmann, Zoraida; Leoni, Massimiliano; Gerardo-Giorda, Luca; Guerra, Jose M. (Frontiers in Medical Technology, 2021)
Background: High-power short-duration (HPSD) recently emerged as a new approach to radiofrequency (RF) catheter ablation. However, basic and clinical data supporting its effectiveness and safety is still scarce. Objective: We aim to characterize HPSD with an advanced virtual model, able to assess lesion dimensions and complications in multiple conditions and compare it to standard protocols. Methods: We evaluate, on both atrium and ventricle, three HPSD protocols (70 W/8 s, 80 W/6 s, and 90 W/4 s) through a realistic 3D computational model of power-controlled RF ablation, varying catheter tip design (spherical/cylindrical), contact force (CF), blood flow, and saline irrigation. Lesions are defined by the 50°C isotherm contour. Ablations are deemed safe or complicated by pop (tissue temperature >97°C) or charring (blood temperature >80°C). We compared HPSD with standards protocols (30–40 W/30 s). We analyzed the effect of a second HPSD application. Results: We simulated 432 applications. Most (79%) associated a complication, especially in the atrium. The three HPSD protocols performed similarly in the atrium, while 90 W/4 s appeared the safest in the ventricle. Low irrigation rate led frequently to charring (72%). High-power short-duration lesions were 40–60% shallower and smaller in volume compared to standards, although featuring similar width. A second HPSD application increased lesions to a size comparable to standards. Conclusion: High-power short-duration lesions are smaller in volume and more superficial than standards but comparable in width, which can be advantageous in the atrium. A second application can produce lesions similar to standards in a shorter time. Despite its narrow safety margin, HPSD seems a valuable new clinical approach.